The Diva Cooks a Goose - Davis, Krista (Davis, Krista. Domestic diva mystery., 2010)
A scrooge steals the gifts from Sophie Winston's family and neighbors, and even takes their holiday meals. She ends the neighbors' finger-pointing by organizing a toy swap for the kids, which restores the spirit of the Christmas season, until a murder enters the picture. With Sophie's detective boyfriend, Wolf, out of town, it's up to Sophie to solve the murder and thefts so that the town's Christmas won't be ruined.